A two-dimensional cobalt(ii) network with a remarkable positive axial anisotropy parameter exhibiting field-induced single-ion magnet behavior. Issue 33 (4th August 2016) - Sun, Lin; Zhang, Sheng; Chen, Sanping; Yin, Bing; Sun, Yichen; Wang, Zhenxing; Ouyang, Zhongwen; Ren, Jianlin; Wang, Wenyuan; Wei, Qing; Xie, Gang; Gao, Shengli
Abstract : With pyridyl-1, 2, 4-triazole (3, 3′-Hbpt), [Co(3, 3′-Hbpt)2 (SCN)2 ]·2H2 On (1 ) and [Ni(3, 3′-Hbpt)2 (SCN)2 ]·2H2 O n (2 ) are prepared and magnetically characterized. Abstract : Based on the 1 H -3-(3-pyridyl)-5-(3′-pyridyl)-1, 2, 4-triazole (3, 3′-Hbpt) ligand, [Co(3, 3′-Hbpt)2 (SCN)2 ]·2H2 O n (1 ) and [Ni(3, 3′-Hbpt)2 (SCN)2 ]·2H2 O n (2 ) have been prepared and structurally determined by single-crystal X-ray crystallography. The Co(ii )/Ni(ii ) ions are bridged by the curved 3, 3′-Hbpt ligands to generate helix chains, further forming a two-dimensional (2D) sheet in which Co(ii )/Ni(ii ) ions are spatially separated from each other by a long spacer 3, 3′-Hbpt ligand. Alternating-current magnetic susceptibility measurements show that the individual octahedral Co(ii ) ions in1 exhibit field-induced slow magnetic relaxation, dominated by a Raman-like process. Compound1 exhibits a very large positive axial anisotropy parameter ( D = +70.1 cm −1 ) and a small transverse anisotropy parameter (| E | = 0.7 cm −1 ) by analysis of direct current magnetic data, which are further confirmed by high-field electron paramagnetic resonance (HF-EPR) spectroscopy and ab initio calculations. Furthermore, the semiconducting behaviors of1 and2 were also studied, which could be used as wide-gap semiconductors.